Riesgo de insolvencia financiera de las empresas del sector manufacturero del cantón Latacunga en el período 2012-2020 - Ninasunta Cando, Erika Lisbeth (2023)
The objective of this research project was to determine the level of financial insolvency risk in companies in the manufacturing sector of the Latacunga canton under the Z1-Altman model in the period 2012 - 2020 with a total of 6 companies with 8 years of continuous activity, through the study of variables through accounting accounts of the financial statements of companies. For this, a methodology with a quantitative approach and a descriptive research level was applied that allowed analyzing the level and behavior of the variables that intervene in the different accounting accounts, with annual time series data, likewise, a documentary design was used. -bibliographic to collect information about the variables, applying an insolvency prediction model called Z1-Altman. Thus, it was possible to verify the effectiveness of the model and analyze the financial situation of the companies.